2012
DOI: 10.2979/philmusieducrevi.20.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Rising to a New Paradigm: Infusing Health and Wellness into the Music Curriculum

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…She states that professional musicians, like athletes, have always faced physical and psychological problems related to their artistic work, due to intense and often solo training, as well as high levels of competition, which extends to student musicians as well. Pierce cites a study that reports 25% of music students entering college or university have higher ratings of depression and anxiety than their non-music peers (Spahn et al 2004in Pierce 2012. Some research has shown that the personalities of those who are drawn to the profession of music are "especially vulnerable to psychological injuries" (Pierce 2012, 155).…”
Section: Editors Diane Conrad and Anitamentioning
confidence: 99%
See 2 more Smart Citations
“…She states that professional musicians, like athletes, have always faced physical and psychological problems related to their artistic work, due to intense and often solo training, as well as high levels of competition, which extends to student musicians as well. Pierce cites a study that reports 25% of music students entering college or university have higher ratings of depression and anxiety than their non-music peers (Spahn et al 2004in Pierce 2012. Some research has shown that the personalities of those who are drawn to the profession of music are "especially vulnerable to psychological injuries" (Pierce 2012, 155).…”
Section: Editors Diane Conrad and Anitamentioning
confidence: 99%
“…This kind of inclusiveness and community is commonly found in participatory musics (Turino 2008) and the subsequent feelings of belonging are a significant predictor of engagement (Bowker et al 2015). However, community is often lacking in North American culture and particularly in university settings that may have large populations and hierarchical, competitive structures (Pierce 2012, Putnam 2000.…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation